Preparing teachers for a changing world what teachers should learn and be able to do - edited by Linda Darling (San Francisco Jossey-Bass, 2005)
Based on rapid advances in what is known about how people learn and how to teach effectively, this important book examines the core concepts and central pedagogies that should be at the heart of any teacher education program. Stemming from the results of a commission sponsored by the National Academy of Education, Preparing Teachers for a Changing World recommends the creation of an informed teacher education curriculum with the common elements that represent state-of-the-art standards for the profession. Written for teacher educators in both traditional and alternative programs, university and school system leaders, teachers, staff development professionals, researchers, and educational policymakers, the book addresses the key foundational knowledge for teaching and discusses how to implement that knowledge within the classroom.
Includes bibliographical references (p. 480-565) and index.
Keywords: Teachers--Training of--United States